Efeito do Kinesio taping sobre a dor, função física, mobilidade, marcha e desempenho muscular de mulheres com osteoartrite de joelhos: um ensaio clínico aleatorizado - Jennifer Granja Peixoto (2015)
Introduction: Osteoarthritis (OA) is one of the most common worldwide musculoskeletal diseases and the joint most commonly affected is the knee. The most common symptom is pain, although there is also loss of function and mobility, and reduced gait speed and performance of the knee and hip muscles. These deficits are more pronounced in women, than in men. Kinesiotaping (KT) is a technique that includes the application of elastic bandages, to reduce pain and stimulate the muscular activity. Objectives: To investigate the effects of the addition of the KT application over the gluteus maximus muscle to the rectus femoris on pain, physical function, functional mobility, gait, and muscular performance in women with bilateral knee OA. Methods: For this pilot blinded randomized controlled trial, 52 women with a mean age of 66±10 years, were randomly allocated to two experimental groups. The experimental group I (EGI) received the KT application over the rectus femoris muscle and the EG II received the KT application over both rectus femoris and gluteus maximus muscles. Pain and perceived physical function were evaluated by the Western Ontario and McMaster University Osteoarthritis Index (WOMAC), functional mobility by the Timed Up and Go test (TUG), temporal spatial gait parameters by the GAITRite system, and isokinetic performance of knee extensors and hip external rotators by the Biodex dynamometer. All outcomes were assessed at baseline and after 48 hours of KT application. Mixed ANOVAs (2X2) with repeated measures, followed by pre-planned contrasts were employed to assess main and interaction effects between the groups and time, with a significance level of 5%. Results: The analyses revealed significant effects of the KT application on pain, perceived physical function, gait speed, and performance of the knee extensor muscles for both groups, without interaction. No effects were observed on measures of functional mobility and performance of the hip external rotators. Conclusions: The addition of the KT application over the gluteus maximus muscle did not result in greater gains, compared to the application over only the rectus femoris muscle. The effects on pain, perceived physical function, and gait speed were statistically and clinically significant. Although statistically significant, the improvements in performance of the knee extensor muscles were probably not clinically relevant.